Improvement of pasture and forage legumes and grasses for Mediterranean climate zones - Nichols P.G.H.; Norton M.R. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Mediterranean climate zone pastures produce valuable animal products and sustain crop production. Well-managed natural grasslands in the Mediterranean basin contain a diversity of species that are adapted to survive the extremes of hot, dry summers and intermittent droughts. Many of these plants have also been introduced to other regions with similar climates, such as southern Australia. Extensive breeding and selection of pasture and forage species in Australia has led to a flourishing seed industry and the resulting cultivars have been sown world-wide in Mediterranean climates. Among the annual legumes, subterranean clover (T. subterraneum) and annual medics (Medicago spp.) have been widely utilised, while several other species have been released recently. Lucerne (M. sativa) is the most important perennial legume in Mediterranean climates, while early flowering, free-seeding white clover (T. repens) types are suited to higher rainfall parts of the zone. The temperate grasses, Lolium perenne, Dactylis glomerata, Festuca arundinacea and Phalaris aquatica, are important in higher rainfall areas of the Mediterranean zone, but require summer dormancy for persistence in drier parts. The summer-active perennial grasses, Megathyrsus maximus, Chloris gayana and Pennisetum clandestinum, have also been sown in parts of southern Australia with milder winter temperatures. Future cultivar improvement will make additional productivity and sustainability gains, particularly utilising local germplasm, but faces the issues of drier and more variable seasons, soil constraints, and greater profitability of cropping. Strong cooperation between scientists in Mediterranean climates and greater vertical integration between basic and applied science will provide the best solutions to farmers, in the face of declining research and development funds.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)